Changing Minds, If Not Hearts : Political Remedies for Racial Conflict - Glaser, James M., 1960-; Ryan, Timothy J. (Book collections on Project MUSE., 2013)
"Americans preach egalitarianism, but democracy makes it hard for minorities to win. Changing Minds, If Not Hearts explores political strategies that counteract the impulse of racial majorities to think about racial issues as a zero-sum game, in which a win for one group means a loss for another. James M. Glaser and Timothy J. Ryan argue that, although political processes often inflame racial tensions, the tools of politics also can alleviate conflict. Through randomized experiments conducted in South Carolina, California, Michigan, Mississippi, Oklahoma, and New Jersey, Glaser and Ryan uncover the racial underpinnings of disputes over affirmative action, public school funding initiatives, Confederate flag displays on government buildings, reparations, and racial profiling. The authors examine whether communities rife with conflict endorse different outcomes when issues are cast in different terms--for example, by calling attention to double standards, evoking alternate conceptions of fairness and justice, or restructuring electoral choices to offer voters greater control. Their studies identify a host of tools that can help overcome opposition to minority interests that are due to racial hostility. Even in communities averse to accommodation, even where antipathy and prejudice linger, minorities can win."--Publisher's description.